Implementation of an Audio Steganography Method for Embedding Secret Messages in Audio Media - Setia Mangiring Marpaung; Rani Rosalinda; Jusnan Pangabean (Sean Institute, 2025)
The rapid development of information technology demands the existence of data security systems capable of protecting confidential information from unauthorized parties. One technique that can be used to maintain information confidentiality is steganography. Steganography is a technique of hiding secret messages within a cover medium so that the existence of the message cannot be directly detected. This study aims to implement an audio steganography method for embedding secret messages into digital audio media. The method used is the Least Significant Bit (LSB), in which the secret message is embedded in the lowest bits of the audio data without significantly altering the audio quality. The research process includes the stages of audio data preparation, secret message embedding, and message extraction. The test results show that the secret message can be successfully embedded and extracted without causing significant changes in audio quality. Therefore, the LSB-based audio steganography method can be used as an effective alternative for data security.